Deteksi Dini PTM Warga Imigran di Malaysia: Skrining TD, Gula Darah, Kolesterol, Asam Urat - Sri Mulyani; Innani Wildania H; Siti Patonah; Wiwik Muhidayati; Novia Dwi A; Fatia Rizki N; Belinda A; Akhmad Huda; Sofyan Hadi H; Fuji Istiana (Jurnal Medika: Medika, 2025)
Worldwide, noncommunicable diseases (NCDs) such as hypertension, diabetes mellitus, hyperuricemia, dyslipidemia, and hyperuricemia are the leading causes of death, including among immigrant communities who often have limited access to health services. Due to economic problems, legal status, and lack of information, Indonesian immigrants living in Malaysia are a vulnerable group who often neglect early detection of their diseases. The purpose of this community service program is to raise public awareness of the risks associated with NCDs and to detect them early through the measurement of blood pressure, blood sugar, total cholesterol, and uric acid levels. In Bukit Sungai Putih Lembah Jaya Utara, Ampang, Selangor, Malaysia, 120 immigrant residents underwent direct health screening and healthy lifestyle training. The results of the community service activity showed that 43.3% of participants had hypertension, 27.5% had above-normal blood sugar levels, 24.2% had hyperuricemia, and 44.2% had high total cholesterol levels. These findings indicate that NCD risk factors are prevalent among immigrants. It is evident that community-based screening helps detect health problems early and encourages broader health efforts. Therefore, to improve the overall health of immigrant residents, sustainable community-based interventions are essential